Training for Academic Librarians in Assistive Technologies (AT) Requires Higher Priority and Targeted Funding / Munyoro, J., Machimbidza, T., & Mutula, S. (2021). Examining key strategies for building assistive technology (AT) competence of academic library personnel at university libraries in Midlands and Harare provinces in Zimbabwe. The Journal of Academic Librarianship, 47(4), Article 102364. https://doi.org/10.1016/j.acalib.2021.102364 - Jasmin, Hilary (Evidence Based Library and Information Practice, 2024)
Objective – To explore strategies for building up library worker abilities in assistive technology (AT) for inclusive implementation. The primary focuses of the study’s interviewing included the extent of existing training, the challenges of funding and executing this type of training, and any notable strategies for creating greater access to high-quality AT training.Design – A qualitative exploratory study of library workers.Setting – Three academic libraries in Zimbabwe.Subjects – Thirty library workers comprised of Senior Library Assistants, Administrative Assistants, and Assistant Librarians.Methods – The researchers conducted semi-structured interviews confidentially over WhatsApp and telephone. They then conducted thematic analysis on the results.Main Results – Exposure to AT training for academic librarians in Zimbabwe is low. Of the 30 librarians interviewed, only 13 had been exposed to any formal AT training. Of those 13, 12 scored their AT training experience as “not very effective.” Primary challenges listed included lack of AT experts as trainers, not enough funding, and ignorance around disability issues.Conclusion – To improve AT expertise in academic librarians, suggestions included integrating AT training into LIS professional education, and for those already in the profession to establish partnerships across academic departments to perhaps leverage more professional AT training across campus. There was also a noted suggestion that hands-on exposure is more beneficial than passive training.